Screening and Selecting of Exopolysaccharide Producing Lactic acid Bacteria from Fermented Thai foods - ตั้งธรรม พีรณัฐ; ฤทธิศร สุจยา; ลาพรหมมา ณัฐวดี; ไชยองค์การ อัจฉรา (Progress in Applied Science and Technology, 2017)
The 300-isolated lactic acid bacteria from fermented foods in Thailand were screened for exopolysaccharide (ESP) producing. The results found that isolated No. 23/14 derived from fermented subterranean ants in Lampang province could produce the highest amount of ESP which the maximum rate was 16.17 g/L. The API 50 CH kits and16S rDNA sequence were used for bacterial strain identification. The isolated No.23/14 showed the similar 16S rDNA sequence as Lactobacillus fermentum at 96.60% and 99.86% respectively. Six difference sugars (sucrose, glucose, mannose, fructose, lactose and xylose) were used for study the optimum carbon source for EPS producing. The best sugar could promote the highest ESP (1.33 g/L) as sucrose. Whereas, ESP yielded was about 0.36-0.45 g/L when using other carbon sources. Examination of monosaccharide composition in ESP produced from sucrose was analyzed by using thin layer chromatography, showed that the ESP was composed of rhamnose, glucose, mannose and fructose.